Control of a permanent magnet synchronous motor fed by a direct AC-AC converter - Sünter, S; Altun, H (Springer, 2005)
This paper presents a Simulink model for the field orientation control of a three-phase permanent magnet synchronous motor (PMSM) fed by a direct AC-AC converter. In the field control scheme, the current and speed controllers are designed using the Internal Model Control (IMC) technique. This means that a time-consuming design procedure is avoided. Field weakening control is also applied to the drive system. Simulation results for the input of the converter with unity input displacement factor are given in addition to the output results. Promising results illustrate that a high performance PMSM fed by an AC-AC converter is achievable.
Keywords: PMSM; matrix converter; IMC; field oriented control